Mode-locked, 1.94-mu m, all-fiberized laser using WS2-based evanescent field interaction - Jung, Minwan; Lee, Junsu; Park, June; Koo, Joonhoi; Jhon, Young Min; Lee, Ju Han (OPTICAL SOC AMER, 2015)
We demonstrate the use of an all-fiberized, mode-locked 1.94 mu m laser with a saturable absorption device based on a tungsten disulfide (WS2)-deposited side-polished fiber. The WS2 particles were prepared via liquid phase exfoliation (LPE) without centrifugation. A series of measurements including Raman spectroscopy, scanning electron microscopy (SEM), and atomic force microscopy (AFM) revealed that the prepared particles had thick nanostructures of more than 5 layers. The prepared saturable absorption device used the evanescent field interaction mechanism between the oscillating beam and WS2 particles and its modulation depth was measured to be similar to 10.9% at a wavelength of 1925 nm. Incorporating the WS2-based saturable absorption device into a thuliumholmium co-doped fiber ring cavity, stable mode-locked pulses with a temporal width of similar to 1.3 ps at a repetition rate of 34.8 MHz were readily obtained at a wavelength of 1941 nm. The results of this experiment confirm that WS2 can be used as an effective broadband saturable absorption material that is suitable to passively generate pulses at 2 mu m wavelengths. (C) 2015 Optical Society of America
Keywords: TOPOLOGICAL INSULATOR BI2SE3; MOLYBDENUM-DISULFIDE MOS2; SATURABLE ABSORBER; MU-M; PULSE GENERATION; CARBON NANOTUBE; OPTICAL-ABSORPTION; ULTRAFAST; GRAPHENE; FEMTOSECOND